Electrolyte Abnormalities in Febrile Seizures - J Gordon Millichap (Pediatric Neurology Briefs)
The role of serum sodium in susceptibility to complicated febrile convulsions was studied in 115 children admitted with simple or complicated febrile convulsions to the Kuopio University Hospital, Finland.